State Museum of Literature Named after Alisher Navoi Fond of “Handwriting and Unique Printing Books” Have Been Saved “Alqofiya” Manuscript - Dekhonov Qutbiddin Nizomiddinovich (Research Parks Publishing LLC, 2021)
areas studied perfectly in the world. The reason is why they learnt it, of course they try to search meaning of Qur’an Karim and Xadis Sharif. When Islam came to our, increasing study it and compare to life events between our ancestors. Including, initial period of learning Qur’an Karim and Xadis Sharif, many scientists especially arabian and iran scientists made books based on arabic grammar and tafsir. If we look at the arabic naxv, the range of this researching works depend on Ali Karamulloh Vajhahu(r.a).